Quadriceps Strength Is Influenced by Skeletal Maturity in Adolescents Recovering From Anterior Cruciate Ligament Reconstruction. Issue 2 (February 2021) - Casp, Aaron J.; Bodkin, Stephan G.; Kew, Michelle E.; Noona, Sean W.; Lesevic, Milos; Hart, Joseph M.; Diduch, David
Abstract : Background: Anterior cruciate ligament injuries and anterior cruciate ligament reconstructions (ACLRs) are common, especially in adolescent patients. Recovery of strength, jumping performance, and perceived/subjective function are often used to make a return to sports decisions after injury. It is unknown how skeletal maturity may influence strength recovery after ACLR. The purpose of this study was to compare the strength and patient-reported outcomes in adolescent ACLR patients with and without open distal femur and proximal tibia physes. Methods: One hundred seventeen consecutive patients under the age of 18 were referred for routine strength and subjective outcomes evaluation following ACLR, 100 were included in the final analyses after excluding those with prior injuries, those tested outside for 4 to 12 month postoperative window, and those with incomplete clinical data. All study patients completed patient-reported outcomes, and underwent isometric and isokinetic testing of knee extensor and flexor strength to calculate normalized peak torque and limb symmetry. Statistical analyses were performed on all outcomes data using a 2×2 (physeal status: open, closed; and sex: male, female) with analysis of covariance where age and preoperative activity level were used as covariates. Results: A significant interaction between sex and physeal status for isokinetic knee extension peak torque and isometric knee extension peak torque, and limb symmetry index was found. This indicated that males with open physes were stronger and more symmetric than males with closed physes and females with open physes at 6 months post-ACLR. There were no differences between sexes for patients with closed physes. No interactions were observed for flexion strength. Male patients and patients with open physes had higher perceived knee function compared with their corresponding counterparts. Conclusions: After ACLR, adolescent patients with open physes had higher quadriceps strength compared with patients with closed physes. Overall, those skeletally less mature patients actually fared better on the functional strength tests, suggesting that functional recovery is not hindered by the presence of an incompletely closed physis. Level of Evidence: Level III—retrospective comparative study.